Stability study of common vasoactive drugs diluted in five types of solutions - Yang, Han; Xiang, Bingbing; Gong, Deiying; Zhao, Guoyan; Zhang, Wensheng (Frontiers in Pharmacology, 2025)
BackgroundVasoactive drugs are widely used during the perioperative period. Different vasoactive drugs have specific recommended solutions for dilution as stated in their instructions, but non-recommended solutions are sometimes used in clinical practice. The impact of using non-recommended solutions on drug stability remains unclear. This study investigated the stability of various commonly used vasoactive drugs diluted with five commonly used solutions—0.9% sodium chloride injection, sodium lactate Ringer’s injection, glucose sodium chloride injection, 5% glucose injection, and 10% glucose injection—under room temperature (24 °C ± 1 °C) without light protection.MethodsEach drug was diluted to clinically common concentrations using the five solutions mentioned above. Five samples of 100 µL each were prepared for each drug. The samples were stored at room temperature without light protection and observed at 0, 2, 4, 6, and 8 h for changes in appearance and pH. High-performance liquid chromatography (HPLC) was used to measure the drug content at each time point. The drug content at 0 h was set as 100%, and the content at other time points was calculated relative to this baseline.ResultsWithin 8 h, all solutions remained clear and transparent. Except for amiodarone hydrochloride, nicardipine hydrochloride, propafenone hydrochloride, and diltiazem hydrochloride, which showed significant pH changes after dilution, the pH changes of the other solutions were less than 0.1. Except for isoproterenol hydrochloride, the content of the other tested drugs showed no significant differences within 8 h.ConclusionWhen diluted with the five commonly used solutions and stored at room temperature without light protection for 8 h, the tested drugs maintained stable properties.